2015
DOI: 10.1152/physiolgenomics.00108.2014
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression changes controlling distinct adaptations in the heart and skeletal muscle of a hibernating mammal

Abstract: Throughout the hibernation season, the thirteen-lined ground squirrel ( Ictidomys tridecemlineatus) experiences extreme fluctuations in heart rate, metabolism, oxygen consumption, and body temperature, along with prolonged fasting and immobility. These conditions necessitate different functional requirements for the heart, which maintains contractile function throughout hibernation, and the skeletal muscle, which remains largely inactive. The adaptations used to maintain these contractile organs under such var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
71
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(81 citation statements)
references
References 108 publications
(107 reference statements)
9
71
1
Order By: Relevance
“…In another study on hibernating squirrels, a significant reduction in myostatin gene expression was found in soleus and diaphragm muscles, which are both resistant to atrophy in this species (Nowell et al, 2011). Other studies have shown reduced levels of myostatin mRNA during hibernation and aestivation, which could be associated with enhanced protein synthesis by facilitating mTOR signalling (Reilly et al, 2013;Vermillion et al, 2015).…”
Section: Regulation Of Protein Synthesismentioning
confidence: 88%
See 2 more Smart Citations
“…In another study on hibernating squirrels, a significant reduction in myostatin gene expression was found in soleus and diaphragm muscles, which are both resistant to atrophy in this species (Nowell et al, 2011). Other studies have shown reduced levels of myostatin mRNA during hibernation and aestivation, which could be associated with enhanced protein synthesis by facilitating mTOR signalling (Reilly et al, 2013;Vermillion et al, 2015).…”
Section: Regulation Of Protein Synthesismentioning
confidence: 88%
“…Despite the need for global suppression of energetically expensive processes such as transcription and translation during dormancy (Storey and Storey, 2010), a number of recent studies have emphasised the importance of maintaining protein synthesis in hibernating muscle through activation of the mTOR signalling cascade (Andres-Mateos et al, 2013;Fedorov et al, 2014;Lee et al, 2010;Nowell et al, 2011). For example, hibernating I. tridecemlineatus were recently shown to exhibit increased expression of genes in the IGF1-AktmTOR signalling pathway (igf1, igf2, akt1, mTOR and rps6kb1), which is associated with the hypertrophic response to increased mechanical loading and is a key pathway promoting protein synthesis (Vermillion et al, 2015). Interestingly, genes encoding IGF-binding proteins, which have known functions in inhibiting protein synthesis, have also been reported to be strongly suppressed in the skeletal muscle of hibernating squirrels and aestivating frogs (Reilly et al, 2013;Vermillion et al, 2015).…”
Section: Regulation Of Protein Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, BAT microRNAs were assessed during torpor in thirteen-lined ground squirrels and those with altered expression were linked to β-oxidation (Wu et al, 2014). Recently, BAT mRNA stability was investigated across the torpor-arousal cycle in thirteen-lined ground squirrels and revealed , cortex and hypothalamus regions of the brain , bone marrow (Cooper et al, 2016), and heart and skeletal muscle (Vermillion et al, 2015a). Measurements shown on the y-axis are means±s.e.m.…”
Section: Post-transcriptional Regulation Of Batmentioning
confidence: 99%
“…It is now possible to analyze the relatedness of the BAT transcriptome with transcriptomes from skeletal muscle (Hampton et al, 2011;Vermillion et al, 2015a) over the course of the hibernation season. Functionally, at the mitochondrial level, skeletal muscle and BAT behave similarly during hibernation (McFarlane et al, 2017; as reviewed by Staples, 2016).…”
Section: Future Directionsmentioning
confidence: 99%